ANALISIS PENGARUH KOMPETENSI KERJA, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN PEMBIAYAAN PADA PT BANK SYARIAH INDONESIA KANTOR CABANG SEMARANG MT HARYONO - Muhammad Habib Sofi; Siti Hasanah; Sam'ani (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to analyze and obtain empirical evidence regarding the effect of competence, compensation, and motivation on the performance of employees in the financing department (a case study at PT Bank Syariah Indonesia, Tbk Semarang Branch Office, MT. Haryono) either simultaneously or partially. The population in this study were all employees of the financing department at PT Bank Syariah Indonesia, Tbk Semarang MT Branch Office. Haryono. The sampling technique used saturated sampling, as many as 35 respondents. The data used in this study is primary data obtained through the distribution of questionnaires. The data analysis model uses Multiple Linear Regression Analysis Model. Meanwhile, the data analysis technique used the F Statistical Test, the Coefficient of Determination (R2), and the t-Statistical Test. The results of the analysis and discussion show that the variables of competence, compensation, and motivation simultaneously have a significant effect on the performance of employees in the financing department at PT Bank Syariah Indonesia, Tbk Semarang MT Branch Office. Haryono. Partially, the variables of competence, compensation, and motivation each have a positive and significant effect on the performance of employees in the financing department at PT Bank Syariah Indonesia, Tbk Semarang MT Branch Office. Haryono. Keywords: Employee Performance in Financing, Competence, Compensation, Motivation.